Presence Application on Nagari Devices Using Android-Based Qr Code: Aplikasi Presensi Perangkat Nagari Menggunakan Qr Code Berbasis Android - Revo Abdi Sabda; Yusran Yusran; Dwi Winarti (Perkumpulan Doktor Indonesia Maju (PDIM), 2022)
Applications that are growing rapidly have provided various benefits in various agencies. The office of the Mayor of Nagari Koto Gadang is a government agency whose attendance system for Nagari devices is still done manually using a note. In this study, researchers designed an attendance application using a QR Code which was implemented at the Office of the Mayor of Nagari Koto Gadang utilizing a manual presence system towards a digital system. This application is built with a high level of mobility that utilizes a smartphone device as a media presence. The development method used in the Nagari device presence system uses the Waterfall Model, the design uses UML. The application functions as a QR Code. With this application, the Nagari device presence process is carried out using a smartphone device as a medium. This makes the attendance process easier by using the presence application using an Android-based QR Code. In its implementation, the application will also use Kodular as a function to make scans on smartphone devices.